Pengaruh Risk Profile, Good Corporate Governance, Earnings dan Capital pada Perubahan Harga Saham Bank - Cahyani, Ni Putu Desy Wulandara; Putri, IG.A.M Asri Dwija (E-Jurnal Akuntansi; Vol 25 No 2 (2018), 2018)
Stock is one of the financial instruments used by the company to obtain capital in an effort to strengthen its financial position. The demand for shares is largely determined by the performance of companies such as financial performance, risk handling within the company and the implementation of good corporate governance. Therefore, the bank must maintain and optimize the performance of the company, so that more investors are investing their funds in bank shares that have an impact on the increase of bank stock price. The study is aimed to determine the effect of risk profile, good corporate governance, earnings measured by return on assets and net interest margin and capital measured by capital adequacy ratio on bank stock price changes. The research was conducted at the banking companies registered at the Indonesian Stock Exchange in 2014-2016 with the total samples of 28 banking companies determined by purposive sampling method. The data analysis technique used was multiple linear regression. The results of this study indicated that the risk profile has a negative effect of bank stock prices changes. Moreover, good corporate governance, return on assets and net interest margin has a positive effect of bank stock prices changes. The capital adequacy ratio has no effect on bank stock price changes. Keywords : bank stock price changes, risk profile, good corporate governance, return on assets, net interest margin and capital adequacy ratio